Cover Picture: Comparison of Reductive Ligation‐Based Detection Strategies for Nitroxyl (HNO) and S‐Nitrosothiols (ChemistryOpen 2/2016) - Miao, Zhengrui (ChemistryOpen, 2016)
The front cover picture shows a prefluorescent phosphine‐based probe reacting with nitroxyl (HNO) and S‐nitrosothiol (RSNO), nitrogen oxide‐derived biological signals. Both species react with the prefluorescent probe, but only the product from the HNO reaction can complete a further chemical ligation pathway that results in fluorescence, indicating the presence of HNO. The product of the probe with RSNO does not complete this ligation and does not generate a fluorescent species. These phosphine‐based probes thus demonstrate a selectivity for HNO over RSNO based on their chemical reactivity and can be used in biological systems to differentiate these species. More information can be found in the Communication by S. Bruce King and Z. Miao on page 110 in Issue 2, 2016 (DOI: 10.1002/open.201500200).[Image: see text]